La Problematique De Gestion Du Parc National De La Comoe (Pnc) En Cote D’ivoire, Entre La Survie Des Populations Riveraines Et La Conservation De La Biodiversite - Kady, Koueita Mariam Konaté; Moussa, Diomandé; Nicolas, Brou Ahossi (European Scientific Journal, ESJ, 2018)
The Comoé National Park (CNP), the largest park in West Africa, is one of the twenty largest parks in the world. It undergoes many anthropics pressures, the most intense of its history have been those periods of sociopolitical crisis that Côte d’Ivoire has experienced. The anthropogenic pressures that weigh on this park are most often practiced by the riparian populations for their survival. These pressures are rife despite the State’s investigations through the Ivorian Office of Parks and Reserves (OIPR), the structure in charge of the management of protected areas. In view of this situation, a fundamental question arises, how to achieve sustainable conservation of the park’s biodiversity without depriving riparian populations of their survival? This study mainly allows to analyze the factors at the origin of the management problem of this park. Through a qualitative approach as well as the appropriate data collection techniques and tools, we identify the problems from three main angles, namely the socio-cultural, economic and institutional characteristics that underlie the sustainable management problem of the CNP.